Microstructure and Mechanical Properties of 4343/3003/6111/3003 Four-Layer Al Clad Sheets Subjected to Different Conditions - Minglong Kang; Li Zhou; Yunlai Deng; Yajun Luo; Maoqing He; Na Zhang; Zhonghua Huang; Lijun Dong (Metals, 2022)
To meet the lightweight demands of automobiles, Al composite sheets require excellent mechanical properties under the condition of minimal thickness after high-temperature brazing processing. Generally, the standard used Al brazing sheets have a low strength before and after brazing. To overcome this issue, this work develops a novel 4343/3003/6111/3003 four-layer Al clad sheet, whose microstructure and mechanical properties are systematically investigated. The results show the observable fibrous microstructure with elongated grains parallel to the rolling direction in the developed four-layer Al clad sheet of the cold-rolled and annealed states. After brazing, this fibrous microstructure transforms into coarse equiaxed grains. In addition, the 4343 layer is the brazing layer. Si is mainly distributed in the 4343 layer of the cold-rolled Al clad sheets, whereas Si penetrates into the core layer along the grain boundaries after brazing. The cold-rolled samples present a certain brittleness from fracture morphology, whereas the final annealed ones show a typical ductile fracture. Meanwhile, the typical intergranular fracture is visible after brazing. The mechanical properties of the Al clad sheets are improved after brazing, with an increase of 76% in tensile strength and 62% in yield strength, compared with the final annealed ones. The elongation is increased by 29% compared with that of the cold-rolled ones. This study provides a theoretical basis for further improvement of the strength of aluminum honeycomb panels.